2008
DOI: 10.1016/j.jchromb.2008.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Application of the accurate mass and time tag approach in studies of the human blood lipidome

Abstract: We report a preliminary demonstration of the accurate mass and time (AMT) tag approach for lipidomics. Initial data-dependent LC-MS/MS analyses of human plasma, erythrocyte, and lymphocyte lipids were performed in order to identify lipid molecular species in conjunction with complementary accurate mass and isotopic distribution information. Identified lipids were used to populate initial lipid AMT tag databases containing 250 and 45 entries for those species detected in positive and negative electrospray ioniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 53 publications
1
40
0
Order By: Relevance
“…Indeed we have obtained confi rmatory MS/MS product ion spectra for representatives of many of the lipid subclasses identifi ed in this study (data not shown). Identifi cation confi dence has also been shown to be enhanced with the incorporation of retention time criteria into the database searching process in the presence of internal standards that allow for normalization of retention times (53)(54)(55)(56). Thus, performing MS/MS analyses in a spot-check fashion would allow for further retention time curation of the searchable database fi les, and this could easily be developed through an iterative process within a laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed we have obtained confi rmatory MS/MS product ion spectra for representatives of many of the lipid subclasses identifi ed in this study (data not shown). Identifi cation confi dence has also been shown to be enhanced with the incorporation of retention time criteria into the database searching process in the presence of internal standards that allow for normalization of retention times (53)(54)(55)(56). Thus, performing MS/MS analyses in a spot-check fashion would allow for further retention time curation of the searchable database fi les, and this could easily be developed through an iterative process within a laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…By observing this table closely (Table S1 in the Supporting Information) it is obvious that the top 10 most abundant ions (Table S2 in One approach that can be used to obtain MS 2 information is to carry out data-dependent experiments. 40 During datadependent experiments it is possible to collect MS and MS 2 data in a serial process, that is when a specific ion of interest is detected in full scan mode and after a specific set of criteria, for example, peak intensity, retention time, inclusion-and/or exclusion criteria, are met, the mass spectrometer will switch to MS 2 mode and collect fragment-ion data. However, during these experiments for complex samples coelution of multiple lipids, at low and high level concentrations will occur, and the data-dependent fragmentation experiments may vary from sample to sample.…”
Section: Ps (40) Lpc (22) Fa (14) Pi (7) Choe (6) Pe (4) Pg (3)mentioning
confidence: 99%
“…It stores mainly triacylglycerol (TAG), which provides energy for plant metabolism (Ding et al, 2008). Oil body binding protein is a kind of proteins binding the surface of oil body in the developing embryos, including the oleosin, caleosin, and steroleosin.…”
Section: Up-regulation Of Fatty Acid Synthesis During Seed Developmenmentioning
confidence: 99%